Hepatoprotective Effect of Ethanolic Extract of Capsicum Annuum L. (Red Variety) on Paracetamol Induced Hepatotoxicity in Long Evans Rats - Sultana, Sadia; Khanam, Masuma; Nahar, Kamrun; Israt, Ummey Honey; Ahmed, Shehreen; Jahan, Israt (Mugda Medical College Journal, 2022)
Background: Paracetamol induced hepatotoxicity is a critical problem. Plant products like Capsicum annuum, are known as an excellent source of flavonoids and phenolics, which are important antioxidant components that reduce the risk of such condition and ensures hepatoprotection. Objectives: To evaluate the hepatoprotective effect of ethanolic extract of Capsicum annuum L. (red variety) and to compare its hepatoprotective activity with Silymarin. Methods: This experimental study was performed on 35 rats which were taken for the study and divided in 7 groups, each group containing 7 rats. Hepatotoxicity was introduced by Paracetamol at a dose of 750 mg/kg every 72 hourly, and it was given to all except control group. Silymarin was given as standard. G-I rats served as control, G-II served as hepatotoxic control and given Paracetamol. G-III rats were given Silymarin at the dose of 50 mg/kg/day. G-IV and G-V rats were given extract of capsicum at a dose of 250 mg/kg and 500mg/kg daily. After completion of 21 days experiment, all the rats were sacrificed under chloroform anesthesia and blood and liver samples were collected. Biochemical parameters e.g., serum bilirubin, ALT and AST were estimated and histopathological examination of the liver of the rats was also done. Results: Mean serum bilirubin, ALT and AST levels of paracetamol treated group increased significantly which were highest among all groups. All the parameters were improved with treatment of capsicum and the best result was observed with high dose of extract of capsicum which was similar to silymarin. Microscopic examination of liver tissues showed centrilobular necrosis, periportal fibrosis and loss of cellular architecture in G-II. Bridging fibrosis with improvement of necrosis were found in G-III and G-V. Conclusion: Pretreated ethanolic extract of Capsicum annuum L. (red variety) has hepatoprotective activity, which is almost similar to Silymarin. Mugda Med Coll J. 2022; 5(1): 19-23